2007
DOI: 10.1371/journal.pbio.0050241
|View full text |Cite
|
Sign up to set email alerts
|

Ten_m3 Regulates Eye-Specific Patterning in the Mammalian Visual Pathway and Is Required for Binocular Vision

Abstract: Binocular vision requires an exquisite matching of projections from each eye to form a cohesive representation of the visual world. Eye-specific inputs are anatomically segregated, but in register in the visual thalamus, and overlap within the binocular region of primary visual cortex. Here, we show that the transmembrane protein Ten_m3 regulates the alignment of ipsilateral and contralateral projections. It is expressed in a gradient in the developing visual pathway, which is consistently highest in regions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
232
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(248 citation statements)
references
References 57 publications
16
232
0
Order By: Relevance
“…Indeed, our real-time PCR experiment confirms that this mutation is a complete null in our patients, whereas the Odz3−/− mice have only 76% reduction in the transcript. 23 Although previous studies have shown robust expression in the optic stalk-suggesting that, as in Drosophila, ODZ3 plays a very early role in eye development-we note that marker studies are needed to delineate the exact nature of that developmental role.…”
Section: Homozygous Null Mutation In Odz3 | Aldahmesh Et Almentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, our real-time PCR experiment confirms that this mutation is a complete null in our patients, whereas the Odz3−/− mice have only 76% reduction in the transcript. 23 Although previous studies have shown robust expression in the optic stalk-suggesting that, as in Drosophila, ODZ3 plays a very early role in eye development-we note that marker studies are needed to delineate the exact nature of that developmental role.…”
Section: Homozygous Null Mutation In Odz3 | Aldahmesh Et Almentioning
confidence: 85%
“…22 Surprisingly, however, Odz3 knockout mice have grossly normal eyes but significantly impaired binocular vision due to abnormality in mapping ipsilateral projections in the optic pathway. 23 However, it must be noted that only the transmembrane region of the Odz3 was deleted in the knockout construct, so the allele is likely hypomorphic. The mutation we identified in ODZ3 in a family with autosomal recessive microphthalmia is the strongest evidence to date that the role of odz in early eye morphogenesis in Drosophila is probably conserved in mammals.…”
Section: Homozygous Null Mutation In Odz3 | Aldahmesh Et Almentioning
confidence: 99%
“…The crucial difference between the abnormal binocular and normal monocular visuomotor responses is activation (or not, respectively) of the incoherent input from the misaligned ipsilateral and contralateral projections. Because mismatch of eye-specific input may induce interocular suppression (Sherman, 1974;Leamey et al, 2007), occluding one eye presumably removes one incompatible source, and therefore suppression, allowing the remaining contralateral input to mediate normal optomotor responses. The result is consistent with studies showing impaired visuomotor behavior in albino mice which have reduced ipsilateral projections (Balkema et al, 1981), and in rabbits when the anterior visual field is masked (Collewijn et al, 1978).…”
Section: Contralateral and Ipsilateral Sc Input Contributes To Visuommentioning
confidence: 99%
“…Ten m is also expressed in the central nervous system (CNS) of Drosophila (Levine et al 1997;Minet et al 1999), as is the related protein Ten a (Fascetti and Baumgartner, 2002;Rakovitsky et al 2007). The single teneurin of C. elegans, ten-1, is required for the normal development of the gonad and the fasciculation of subsets of axons (Drabikowski et abnormal pathfinding of axons at the optic chiasm resulting in the loss of binocular vision (Leamey et al 2007).…”
mentioning
confidence: 99%